2013
DOI: 10.1097/opx.0b013e3182780bfd
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of On- and Off-Axis Eye Length Measurements Using the Lenstar

Abstract: Purpose To determine the repeatability of eye length measurements made centrally and off-axis using a low-coherence interferometer. Methods Eye length was measured (left eye) in twenty-nine adults with a Haag-Streit Lenstar LS 900. Five measurements were made centrally, 10° temporally, and 10° nasally on the retina by the same examiner at two separate visits. Inter-visit repeatability was assessed by plotting the difference versus the mean of each pair of measurements (bias) and calculating the 95% limits of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 25 publications
(32 reference statements)
4
26
0
Order By: Relevance
“…However, the CoR of AL was higher than that obtained by the IOLMaster and Lenstar. 9, 10 In the present study, rather than using of group refractive index, AL was the sum of CCT, ACD, LT and VL. The bias of each element may affect the AL measurement.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the CoR of AL was higher than that obtained by the IOLMaster and Lenstar. 9, 10 In the present study, rather than using of group refractive index, AL was the sum of CCT, ACD, LT and VL. The bias of each element may affect the AL measurement.…”
Section: Discussionmentioning
confidence: 97%
“…These methods are used by the IOLMaster (Carl Zeiss Meditec, Dublin, CA) 7, 8 and Lenstar (Haag-Streit USA, Mason, OH); these imaging modalities can only make axial measurements in a single dimension, similar to the A-scan ultrasound. 911 Most of the devices do not have a fixation target and use the group index for converting optical length to geometrical length. 10, 3234 These measurements of axial length may thus be influenced by changes due to accommodation during measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With four reference mirrors, the full-length ocular biometry was sequentially obtained, which may be used for the precise measurement of the axial length and intraocular lens calculation. Compared with IOLMaster (Carl Zeiss Meditec, Dublin, CA) or LENSTAR (Haag-Streit USA, Mason, OH) [31,32], the two-dimensional image of each component element of the anterior segment and the retinal image were obtained during the biometric measurement, although the repeatability and accuracy of each part was not validated. For some hyperopes with a short axial length, the retinal image was also present in the image obtained with the fourth mirror position.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that LE agreement with SM and UP is excellent and this, added to the ease of its use and its noninvasiveness, results in a very promising tool [23,30]. Moreover, for LE and SM proper alignment has shown to be easier and less time-consuming than for UP and PC [21].…”
Section: Discussionmentioning
confidence: 99%